2020
DOI: 10.3389/fnut.2020.593436
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite Fingerprinting of Kersting's Groundnut [Macrotyloma geocarpum (Harms) Maréchal & Baudet] Seeds Using UPLC-qTOF-MS Reveals the Nutraceutical and Antioxidant Potentials of the Orphan Legume

Abstract: The identification and subsequent quantification of phenolic compounds in plants is the first step toward harnessing their associated nutritional and health benefits. Due to their diverse phenolic compound compositions, grain legumes are known for their high nutritional and health values. The aim of this study was to assess the inter-variations in chemical composition, phytochemical content, and antioxidant capacity of seed extracts from eight Kersting's groundnut [Macrotyloma geocarpum (Harms) Marechal &a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 66 publications
1
5
0
Order By: Relevance
“…This argument is supported by the findings of Hungria and Phillips (1993) who also showed that a black-seeded common bean genotype that released higher concentrations of nod-geneinducing flavonoids elicited greater nodulation than its isogenic cream genotype with reduced biosynthesis of the flavonoid nodgene inducers. Therefore, the markedly higher concentrations of anthocyanins and flavonoids found in the seedcoats of black cowpea and Bambara groundnut landraces (Tsamo et al, 2019(Tsamo et al, , 2020 probably induce greater nod-gene expression in the microsymbionts of these species, leading to increased nodulation and N 2 fixation, as found in this study (Tables 4, 5).…”
Section: Effect Of Seedcoat Pigmentation On Nodulation and Symbiotic N Nutrition Of Bambara Groundnut Landracessupporting
confidence: 60%
See 2 more Smart Citations
“…This argument is supported by the findings of Hungria and Phillips (1993) who also showed that a black-seeded common bean genotype that released higher concentrations of nod-geneinducing flavonoids elicited greater nodulation than its isogenic cream genotype with reduced biosynthesis of the flavonoid nodgene inducers. Therefore, the markedly higher concentrations of anthocyanins and flavonoids found in the seedcoats of black cowpea and Bambara groundnut landraces (Tsamo et al, 2019(Tsamo et al, , 2020 probably induce greater nod-gene expression in the microsymbionts of these species, leading to increased nodulation and N 2 fixation, as found in this study (Tables 4, 5).…”
Section: Effect Of Seedcoat Pigmentation On Nodulation and Symbiotic N Nutrition Of Bambara Groundnut Landracessupporting
confidence: 60%
“…Seedcoat pigmentation is reported to be a major determinant of the profile and concentrations of flavonoids, anthocyanins and anthocyanidins in cowpea, Bambara groundnut and Kersting's groundnut seeds (Tsamo et al, 2018(Tsamo et al, , 2019(Tsamo et al, , 2021. Based on metabolite profiling of cowpea seed coats, as well as Bambara groundnut and Kersting's bean seeds, Tsamo et al (2020) found black seeds of legumes to be a natural source of nutraceuticals for human consumption, and a reservoir of anthocyanins that can be exploited for developing cosmetic, food and pharmaceutical products.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Legume seeds contain significant amounts of antioxidants due to their high phenolic, flavonoid, and anthocyanin contents. Consuming products made from these legumes may help prevent and manage various chronic and degenerative diseases, as well as address proteincalorie malnutrition (Foyer et al, 2016;Tsamo et al, 2020;Popoola et al, 2022a). Studies by Adefegha and Oboh (2012); Kennedy (2014); Adefegha et al (2017); Gupta and Prakash (2019), and Adefegha (2018) have confirmed that these bioactive components of NULs could play significant roles in increasing the immune level and support prevention of common diseases such as malnutrition (severe and acute particularly in infants), sexual enhancers, obesity, diabetes, heart-related diseases amongst others.…”
Section: Bioactive Components Of Underutilized Legumesmentioning
confidence: 99%
“…Phenolic compounds are hydroxylated substances naturally found in foods (Achkar et al, 2013). They are of plant origin (Tsamo et al, 2020), having a pigmentation function (Singh et al, 2019), free radical removal (Koley et al, 2014) and light absorption in plants (Naczk & Shahidi, 2004). The value of phenolic compounds for sourdoughs is related to larger wheat flour, being considered a source of phenolic compounds (Sivam et al, 2010).…”
Section: Evaluation Of Ph Contents Of Total Phenolic Compounds and An...mentioning
confidence: 99%